14-3-3 protein binding blocks the dimerization interface of caspase-2 - Kalabova, Dana; Filandr, Frantisek; Alblova, Miroslava; Petrvalska, Olivia; Horvath, Matej; Man, Petr; Obsil, Tomas; Obsilova, Veronika (The FEBS journal, 2020)
Among all species, caspase-2 (C2) is the most evolutionarily conserved caspase required for effective initiation of apoptosis following death stimuli. C2 is activated through dimerization and autoproteolytic cleavage and inhibited through phosphorylation at Ser139 and Ser164 , within the linker between the caspase recruitment and p19 domains of the zymogen, followed by association with the adaptor protein 14-3-3, which maintains C2 in its immature form procaspase (proC2). However, the mechanism of 14-3-3-dependent inhibition of C2 activation remains unclear. Here, we report the structural characterization of the complex between proC2 and 14-3-3 by hydrogen/deuterium mass spectrometry and protein crystallography to determine the molecular basis for 14-3-3-mediated inhibition of C2 activation. Our data reveal that the 14-3-3 dimer interacts with proC2 not only through ligand-binding grooves but also through other regions outside the central channel, thus explaining the isoform-dependent specificity of 14-3-3 protein binding to proC2 and the substantially higher binding affinity of 14-3-3 protein to proC2 than to the doubly phosphorylated peptide. The formation of the complex between 14-3-3 protein and proC2 does not induce any large conformational change in proC2. Furthermore, 14-3-3 protein interacts with and masks both the nuclear localization sequence and the C-terminal region of the p12 domain of proC2 through transient interactions in which both the p19 and p12 domains of proC2 are not firmly docked onto the surface of 14-3-3. This masked region of p12 domain is involved in C2 dimerization. Therefore, 14-3-3 protein likely inhibits proC2 activation by blocking its dimerization surface. DATABASES: Structural data are available in the Protein Data Bank under the accession numbers 6SAD and 6S9K.
Keywords: Protein Binding; Protein Isoforms; Recombinant Proteins; krystalografie rentgenová; mutace; multimerizace proteinu; vazebná místa; protein-protein interaction; Caspase 2; H/D exchange; fosforylace; Phosphorylation; 14-3-3 protein; protein - isoformy; molekulární modely; Crystallography, X-Ray; kaspasa 2; rekombinantní proteiny; Models, Molecular; vazba proteinů; Binding Sites; crystallography; lidé; proteiny 14-3-3; konformace proteinů; Humans; Protein Conformation; 14-3-3 Proteins; Mutation; Protein Precursors; proteinové prekurzory; caspase-2; Protein Multimerization